Persepsi Pelaku Usaha Gula Merah Atas Pentingnya Laporan Keuangan untuk Memprediksi Kelangsungan Usaha - Handriyani Dwilita; Pipit Buana Sari (ARBITRASE: Journal of Economics and Accounting, 2023)
MSME problems include marketing, product development, financial management, human resource quality and technology. Managing business finance is an important point that can support maximizing the progress of MSME businesses, but not infrequently financial management does not receive special attention and tends to be ignored. One form of financial management that has been carried out is the availability of reliable business financial reports as accounting information to support financial decision making. This study aims to dig deeper into the perceptions of brown sugar business actors in 10 Kota Pari villages, Deli Serdang Regency. The research results are expected to be one of the answers that provide an overview of the condition of MSME actors and provide answers to the unavailability of financial reports for most of the MSME in Indonesia. This research is a qualitative descriptive study, using interview techniques to 10 samples selected using purposive sampling method. The results of the study revealed that overall the perception of brown sugar business actors on the importance of financial reports for predicting business continuity is still very low